Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Pakan Alternatif Amoniasi Jerami Jagung di Nagari Pelangai Kaciak Kecamatan Ranah Pesisir, Pesisir Selatan - Tinda Afriani; Yoga Seftiadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
Roughage has been needed for main source of ruminant’s feeding. However the main obstacle faced by farmers during the dry season is an availability of fresh forage feed, which is only corn straw. They have lack skill of fermentation technique of roughage to increase its quality and period of storage. The purpose of this activity was to provide knowledge and skills for farmers in terms of management and utilization of agricultural waste such as corn straw. This activity was carried out both counseling and training method of ammoniation of corn straw by farmer in Nagari Pelangai Kaciak, Ranah Pesisir District, Pesisir Selatan - West Sumatra. The result of this activity was transformation process of certain knowledge from academia to farmer, so as they understood a reason for doing ammoniation step. It was expected that having multiply impacts for surrounding, for instance not only rising quality of corn straw, but also improving livestock’s management and providing friendly environment.